SMART E-LEARNING OPTIONS FOR STUDENTS IN MEDICAL RESIDENCY AND CLERKSHIP DURING THE COVID-19 PANDEMIC - zulfiqqar, Andy; Ahmad Zulfan Hendri; Soeroharjo, Indrawarman (Indonesian Urological Association, 2023)
Objective: This study aimed to evaluate medical resident and clerkship preferences for a variety of available Smart e-Learning options to better cope with this global pandemic. Material & Methods: This cross-sectional study using a web-based national survey was conducted between the 10th-20th of June 2020. As many as 91 of 200 (45.5% response rate) residents and clerks, who were randomly invited, responded to the survey and rated the available modalities for Smart e-Learning. Results: Generally, respondents choose morning scientific online meetings (rated 7.61/10), webinars on case discussion (7.58/10), and pre-recorded tips and tricks on surgery (7.32/10) as their favorite modalities of Smart e-Learning. Conclusion: Scientific meetings among faculty and video based learning are both equally favorite modalities of Smart e-Learning during this pandemic. Meanwhile, morning reports are the least favorite due to the majority of cases are emergency cases that lack interactive discussion. This study may provide more insights for medical faculties into how to better cope with this pandemic and continue to deliver high quality education in the ‘New Normal’ Era using Smart e-Learning options. Keywords: e-Learning, resident, clerkship, New Normal Era.